The Power of Peers: Prompting Savings Behavior Through Social Comparison. Issue 1 (2nd January 2020) - Raue, Martina; D'Ambrosio, Lisa A.; Coughlin, Joseph F.
Abstract: In 2 experimental studies (Study 1: n  = 1, 155; Study 2, n  = 630), the authors used a social norms approach to promote savings behavior. Many people do not save enough for retirement, which may be due to uncertainty about the future or saving plans. Making social comparisons can reduce uncertainty and upward comparisons can provide the motivation to improve. For this reason, the authors gave participants social feedback on their savings decisions. Participants who were randomly told that they underperformed in comparison with their peers were more likely to make changes to their allocation. In Study 1, this group increased their savings more than were those who had been categorized among the better performers or overperformers, or who did not receive social information. Participants were generally more likely to change their behavior when they perceived their performance as being average or below average. The results demonstrate that a social comparison approach has the potential to motivate people to start saving for retirement or increase their current savings.